Reaction of sweet orange cultivars expressing the attacin A gene to 'Candidatus Liberibacter asiaticus' infection - Rafaella Teles Arantes Felipe (Pesquisa Agropecuária Brasileira, 2013)
The objective of this work was to evaluate the reaction of four sweet orange cultivars expressing the attacin A gene to 'Candidatus Liberibacter asiaticus' (Las) infection, a bacterium associated to huanglongbing (HLB) disease. Transgenic sweet orange plants of Hamlin, Natal, Pêra, and Valência cultivars, as well as nontransgenic controls received inocula by grafting budwood sections of HLB-infected branches. Disease progression was evaluated through observations of leaf symptoms and by polymerase chain reaction (PCR) analysis, eight months after inoculation. A completely randomized design was used, with four experiments (one for each cultivar) performed simultaneously. Bacteria title was estimated by quantitative PCR (qPCR). HLB symptoms and Las titers were present in nontransgenic and transgenic plants expressing the attacin A gene of the four sweet orange cultivars, eight months after bacteria inoculation. Five transgenic lines (transformation events) of 'Pêra' sweet orange expressing the attacin A gene have significantly lower Las titers in comparison with nontransgenic plants of this cultivar.